Norms in a wired world - Hetcher, Steven A. (Steven Anthony), 1958- (Cambridge studies in philosophy and law., 2004)
Using informal game theory in the analysis of norms and customs, Hetcher breaks new ground by applying his theory of norms to tort law and Internet privacy laws. This book will appeal to students and professionals in law, philosophy, and political and social theory.